Treatment of adult-onset Still’s disease: a review - Jamilloux Y; Gerfaud-Valentin M; Henry T; Sève P (Dove Medical Press, 2014)
Yvan Jamilloux,1–3,* Mathieu Gerfaud-Valentin,1,* Thomas Henry,3 Pascal Sève1 1Department of Internal Medicine, Hôpital de la Croix-Rousse, Université Claude Bernard-Lyon 1, Lyon, France; 2Department of Biochemistry, University of Lausanne, Epalinges, Switzerland; 3International Research Center on Infectiology. INSERM U1111. Université Claude Bernard-Lyon 1, Lyon, France *These authors contributed equally to this work Abstract: Adult-onset Still’s disease (AOSD) is a rare inflammatory disorder that has been recently classified as a polygenic autoinflammatory disorder. The former classification, based on the disease course, seems to be quite dated. Indeed, there is accumulating evidence that AOSD can be divided into two distinct phenotypes based on cytokine profile, clinical presentation, and outcome, ie, a “systemic” pattern and an “articular” pattern. The first part of this review deals with the treatments that are currently available for AOSD. We then present the different strategies based on the characteristics of the disease according to clinical presentation. To do so, we focus on the two subsets of the disease. Finally, we discuss the management of life-threatening complications of AOSD, along with the therapeutic options during pregnancy. Keywords: adult-onset Still’s disease, treatment, anakinra, tocilizumab, canakinumab